Assessment and virtual redesign of a manual handling workstation by computer-aided three-dimensional interactive application. Issue 2 (3rd April 2017) - Ziaei, Mansour; Ziaei, Hojjat; Hosseini, Seyed Younes; Gharagozlou, Faramarz; Keikhamoghaddam, Ali Akbar; Laybidi, Marzieh Izadi; Moradinazar, Mehdi
Abstract : Background . Manual handling of bags which imposes frequent forces and stresses on body parts is a common task that many workers have to perform every day. The present study aimed to assess the postural risk and imposed forces due to manual handling and loading of sugar bags. Methods . This study was conducted on male warehouse workers of a sugar manufacturing plant. Rapid upper limb assessment (RULA) was used to assess the risks of awkward postures and computer-aided three-dimensional interactive application to estimate the forces and moments. Results . RULA final scores were estimated to be 7 and 3 before and after the virtual redesign, respectively. Postures B and E obtained the highest compression forces and moments. The compression forces were higher than the action limit (AL) in all postures before the redesign and exceeded the maximum permissible limit (MPL) in posture E. After the redesign, these forces were reduced below the AL and MPL. Moreover, the shearing forces were lower than the AL and MPL in all postures. Conclusions . The main risk factors were heavy weight and poor control of sugar bags. Virtual redesign can diminish bending and twisting postures, and, therefore, some resulting forces and moments.